2013
DOI: 10.1016/j.vaccine.2013.08.039
|View full text |Cite
|
Sign up to set email alerts
|

The effects of post-exposure smallpox vaccination on clinical disease presentation: Addressing the data gaps between historical epidemiology and modern surrogate model data

Abstract: Decades after public health interventions – including pre- and post-exposure vaccination – were used to eradicate smallpox, zoonotic orthopoxvirus outbreaks and the potential threat of a release of variola virus remain public health concerns. Routine prophylactic smallpox vaccination of the public ceased worldwide in 1980, and the adverse event rate associated with the currently licensed live vaccinia virus vaccine makes reinstatement of policies recommending routine pre-exposure vaccination unlikely in the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 77 publications
3
23
0
Order By: Relevance
“…Therefore, one key advantage to any anti-OPV regimen is the ability to protect following exposure to the virus. Several antiviral drugs have been demonstrated to provide post-exposure protection in animal models (Nalca et al, 2008;Parker et al, 2008b,c;Quenelle et al, 2007a,c;Smith et al, 2011;Stabenow et al, 2010) and some studies have indicated that smallpox vaccines can also be given post-exposure and still provide protection (Keckler et al, 2013). Others have shown that vaccinating C57BL/6 or BALB/c mice with VACV-Lister (a first-generation smallpox vaccine similar to Dryvax) or ACAM3000 provides post-exposure protection up to 2-3 days post IN ECTV challenge (Paran et al, 2009).…”
Section: Tablementioning
confidence: 99%
“…Therefore, one key advantage to any anti-OPV regimen is the ability to protect following exposure to the virus. Several antiviral drugs have been demonstrated to provide post-exposure protection in animal models (Nalca et al, 2008;Parker et al, 2008b,c;Quenelle et al, 2007a,c;Smith et al, 2011;Stabenow et al, 2010) and some studies have indicated that smallpox vaccines can also be given post-exposure and still provide protection (Keckler et al, 2013). Others have shown that vaccinating C57BL/6 or BALB/c mice with VACV-Lister (a first-generation smallpox vaccine similar to Dryvax) or ACAM3000 provides post-exposure protection up to 2-3 days post IN ECTV challenge (Paran et al, 2009).…”
Section: Tablementioning
confidence: 99%
“…Limited epidemiological data from the smallpox eradication era suggest that vaccination 1 to 3 days following exposure to smallpox might be effective at reducing the rate of occurrence and/or severity of smallpox (1,2). Afterwards, vaccine efficacy appears to progressively decline throughout the incubation phase of the disease (ϳ12 days), and vaccination appears to be wholly ineffective following onset of clinical symptoms.…”
mentioning
confidence: 99%
“…Yet, the concomitant use of these drugs, during the 468 course of treatment, does not allow to determine their sole efficacy in those cases. 469 Although the above data strongly support the use of these drugs for treatment of The feasibility of postexposure vaccination against smallpox is based on historical 480 anecdotal data, and on recent publications using surrogate animal models 34,[87][88][142][143] .…”
mentioning
confidence: 99%
“…The cumulative data, considering gaps arising from limited epidemiological data and 482 the ability to correlate data from surrogate animal models, suggest that active 483 vaccination up to 4 days postexposure is protective 54,87,[144][145][146] . However, as already 484 discussed, in a population scale, the unknown exposure rate and the limited supply, human, and the extremely short incubation period of about 2-3 days is much shorter 497 than in the human disease (7-14 days).…”
mentioning
confidence: 99%
See 1 more Smart Citation